homework6sol.20100303.4b8eff99de8384.47843235

homework6sol.20100303.4b8eff99de8384.47843235 - 5 Here T =...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
TAM 412, Homework 6, Selected answers Harry Dankowicz Mechanical Science and Engineering University of Illinois at Urbana-Champaign [email protected] 3. By Newton’s second law it follows that m 1 ¨ r 1 = r 1 U ( r 2 r 1 ) m 2 ¨ r 2 = r 2 U ( r 2 r 1 ) where r 1 U ( r 2 r 1 ) refers to the gradient of U with respect to the cartesian components of the position vector r 1 from the origin of some coordinate system to the f rst particle. But r 2 U ( r 2 r 1 )= r 1 U ( r 2 r 1 )= r U ( r ) , where r = r 2 r 1 .Thu s ,w i th( m 1 + m 2 ) r cm = m 1 r 1 + m 2 r 2 it follows that ¨ r cm = 0 , i.e., the acceleration of the center of mass is independent of U .A l so , d 2 dt 2 m 2 r = r μ m 2 m 1 +1 U ( r ) , 4. Here T = m 2 ¡ ˙ x 2 1 + ˙ y 2 1 ¢ + M 2 ¡ ˙ x 2 2 + ˙ y 2 2 ¢ and U = mgy 1 + Mgy 2 where x 1 = a sin θ ,y 1 = a cos θ x 2 = x 1 + b sin ϕ ,y 2
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 5. Here T = m 2 ¡ ˙ x 2 + ˙ y 2 + ˙ z 2 ¢ and U = mgz where x = z cos θ ,y = z sin θ The equation of motion corresponding to θ yields z 2 ˙ θ = h where h is some constant (which depends on initial conditions and the mass). 6. Here T = m 2 ¡ ˙ x 2 P + ˙ y 2 P ¢ + m 2 ˙ h 2 1 + m 2 ˙ h 2 2 and U = mgy P + mgh 1 + mgh 2 where x P = 4 b 2 + PA 2 − PB 2 4 b ,y P = − p PA 2 − x 2 h 1 = − ( a − PA ) ,h 2 = − ( a − PB ) Note, the T in the question is the f rst term in the expression above. 1...
View Full Document

Ask a homework question - tutors are online